Famine, bad weather and political alliances: Siena and Manfredi of Sicily between 1257 and 1260 (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
The famine that plagued Europe in the period 1257-1260, caused by the eruption of the Indonesian volcano Samalas, is analyzed in this contribution from the point of view of Sienese public sources. What emerges is that the Tuscan city, in comparison to other northern Italian communes, proved readier to manage this emergency because of the measures it had put in place to combat and prevent food crises during a previous famine, which had affected Tuscany in the period 1248-1256. Siena also managed to turn this emergency to its favor in the context of foreign policy, using the necessity to buy wheat from southern Italy as a pretext to get politically closer to the Ghibelline Manfred of Sicily, without having to break relations with its Guelph ally Florence. This observation shows how the study of environmental history can be useful not only for socio-economic analyses, but it can also have implications for the history of political events in past societies.
Keywords: Siena; Tuscany; Manfred of Sicily; Famines; Italian Communes; Environmental History